TRUST IN TRANSLATION: A CASE STUDY OF COPYRIGHT AS A LEGAL TRANSPLANT IN THE MUSIC INDUSTRY IN MYANMAR - Valdovinos Kaye, D. Bondy (AoIR Selected Papers of Internet Research, 2019)
This paper highlights non-Western views on trust in regulation and governance through a comparative legal analysis of copyright and the music industry in Myanmar. Legal transplanting, taking a law from one legal system and implanting it, was a common practice throughout colonial history. Standardized copyright, in the form of the TRIPs Agreement, is an example of a post-colonial legal transplant, enforced by the WTO. The South-east Asian nation of Myanmar is the process of a major transition both politically and technologically that is heavily impact its creative industries in general, and music industry in particular. This interdisciplinary comparative legal analysis considers the implications of transplanting copyright regulation into an informal creative economy. Data were collected from fourteen interviews with music industry professionals and legal experts in Myanmar conducted in January 2019. While some informants expressed trust in foreign transplants and a belief in the efficacy of a new copyright law, others expressed concern that these foreign laws would fail to address issues unique to the Myanmar music industry. This study argues that the way forward involves a deeper understanding of the local system of governance.